Analisis Fundamental, Acuan Investasi Saham Jangka Panjang (Dinamis: Jurnal Pengabdian Kepada Masyarakat, 2021)
Stock investors certainly expect maximum profits in their investments in the stock market, both long-term investments and short-term investments. There are two analyzes that can be used to make predictions from the prospect of stock profits. Fundamental Analysis for long term investment and Technical Analysis for short term investment. Understanding the importance of these two analyzes is a provision for investors to be able to analyze, make predictions and then determine which stocks can be profitable now and in the future. The selection of these stocks can add to the investor's portfolio in order to be more productive and get maximum profit. The Community Service Program is focused on the use of fundamental analysis for novice investors, by utilizing the existing financial reports on the IDX web.